Some Inequalities on Submanifolds in Statistical Manifolds of Constant Curvature - Aydin, Muhittin Evren; Mihai, Adela; Mihai, Ion (Univ Nis, Fac Sci Math, 2015)
In this paper, we study the behaviour of submanifolds in statistical manifolds of constant curvature. We investigate curvature properties of such submanifolds. Some inequalities for submanifolds with any codimension and hypersurfaces of statistical manifolds of constant curvature are also established.
Keywords: Statistical manifold; statistical immersion; dual connections; Chen-Ricci inequality